Effects of meals differing in glycemic index on postprandial glucose and insulin levels in individuals with and without type 2 diabetes mellitus - Lau, Zhi Ch'ng (2021)
Postprandial hyperglycemia increases the risk of cardiovascular diseases not only in individuals with type 2 diabetes mellitus (T2DM) and without T2DM. A low glycemic index (GI) diet improved postprandial glycemia, but the results are still inconsistent. Therefore, this study determined the effects of differing meal GI on postprandial glucose and insulin levels in individuals with and without T2DM. This was a randomized crossover study, with a one-week washout period conducted at the endocrine laboratory, Hospital Canselor Tuanku Muhriz (HCTM). A total of 40 individuals participated in the study (T2DM; n=20; without T2DM; n=20). Baseline assessments included anthropometric assessments, biochemical profile, dietary intake, and physical activity level. The test meals designed to be in iso-caloric but different in meal GI. T2DM subjects were asked to attend both test meals with one-week washout period, and without T2DM attended one study visit for a high GI meal, represent the typical meal for the general population. The testing procedures based on the meal- challenge test (MCT) techniques for glucose and insulin responses. Fasting blood was obtained at 0 minutes, followed by eating the test meals for 20 minutes. Subsequent blood samples were obtained at 30, 60, 120, 180 and 240 minutes. At baseline, T2DM subjects had higher body mass index (BMI), waist circumference, blood pressure, glycemic profiles, lower total and LDL-cholesterol, higher dietary fat and fibre intake compared to without T2DM. After consuming the high GI meal, the postprandial glucose response in T2DM was significantly higher at all time points than without T2DM (p<0.001). T2DM had a significantly higher glucose incremental area n without T2DM (p<0.001). T2DM had significantly lower insulin level at 30 minutes (p<0.05) and higher insulin levels at 180 and 240 minutes (p<0.001) than without T2DM. There were no significant differences in insulin iAUC at 240 minutes between T2DM and without T2DM. In T2DM, there were no significant difference between the glucose profiles over time between the two meals. However, low GI meal produced higher insulin responses at 30 minutes and lower at 180 and 240 minutes than after high GI meal (p<0.05) with no difference in iAUC. In conclusion, T2DM produced higher glucose and insulin response after consuming high GI meals. Meals differing in GI value produced different effects on insulin but not glucose levels. The low GI meal produced lower insulin responses suggesting reduced insulin requirements following low GI meal consumption.